ORIENTATION OF ZAKAT AS HUMANITARIAN ASSISTANCE TO ROHINGYA REFUGEES IN INDONESIA - Kasim, Nur Mohamad; Towadi, Mellisa (UI Scholars Hub, 2018)
The aim of this writing, reviewing the existence of Zakat as humanitarian assistance can be allocated for the Rohingya refugees who are in Indonesia. Given zakat is of national income devoted to indigenous citizens. This writing is normative, is the principal legal study is conceived as norms or rules which apply, both Islamic Law and International Law. Moreover, the authors did a qualitative approach through the study of Islamic law and supported the chart data on Zakat nationally and internationally. In the conclusion showed, firstly, the Rohingya refugees stranded in Indonesia must be given humanitarian aid as well as the Indonesian government to give relief to the citizens Themselves, secondly, Indonesia with the Reviews largest Muslim population Strengthen obligations to protect the Rohingya refugees as solidarity Among fellow Muslims, third, Zakat implicitly also adhere to humanitarian assistances principle, the which is where all the funds collected from individuals is much more efficient assistance as humanitarian aid compared to other humanitarian aid, fourth, Zakat is a source of social financing to increase of the GDP (Gross Domestic Product) of Islamic states and can be relied upon as the primary funding source for humanity.